Proof : - Atkinson, Paul (LexisNexis, 2007)
"Evidence law can be a complex and daunting subject, but this textbook, specifically written for students pursuing a law-related career and for non-lawyers working in the justice system, explains the rules and principles of evidence, and analyses the interaction between statutes and case reports that determine our evidence laws. Also included are self-test questions to assist students in assessing their level of understanding and knowledge of evidence principles. This second edition contains the most recent provincial Court of Appeal and Supreme Court of Canada cases on rulings relating to the use of character evidence, the concept of informer privilege and hearsay, the criteria for holding seperate trials on multiple charges, and evidentiary issues in relation to the Charter"